Activation in the VTA and nucleus accumbens increases in anticipation of both gains and losses - Carter, R. McKell; MacInnes, Jeff J.; Huettel, Scott A.; Adcock, R. Alison (Frontiers in Behavioral Neuroscience, 2009)
To represent value for learning and decision making, the brain must encode information about both the motivational relevance and affective valence of anticipated outcomes. The nucleus accumbens (NAcc) and ventral tegmental area (VTA) are thought to play key roles in representing these and other aspects of valuation. Here, we manipulated the valence (i.e., monetary gain or loss) and personal relevance (i.e., self-directed or charity-directed) of anticipated outcomes within a variant of the monetary incentive delay task (MID). We scanned young-adult participants using functional magnetic resonance imaging (fMRI), utilizing imaging parameters targeted for the NAcc and VTA. For both self-directed and charity-directed trials, activation in the NAcc and VTA increased to anticipated gains, as predicted by prior work, but also increased to anticipated losses. Moreover, the magnitude of responses in both regions was positively correlated for gains and losses, across participants, while an independent reward-sensitivity covariate predicted the relative difference between and gain- and loss-related activation on self-directed trials. These results are inconsistent with the interpretation that these regions reflect anticipation of only positive-valence events. Instead, they indicate that anticipatory activation in reward-related regions largely reflects the motivational relevance of an upcoming event.